2012
DOI: 10.1007/s00442-012-2522-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation in rainforests and cloud forests along a 3,000-m elevation gradient in the Peruvian Andes

Abstract: We report results from a large-scale nutrient fertilization experiment along a "megadiverse" (154 unique species were included in the study) 3,000-m elevation transect in the Peruvian Andes and adjacent lowland Amazonia. Our objectives were to test if nitrogen (N) and phosphorus (P) limitation shift along this elevation gradient, and to determine how an alleviation of nutrient limitation would manifest in ecosystem changes. Tree height decreased with increasing elevation, but leaf area index (LAI) and diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
165
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(186 citation statements)
references
References 76 publications
13
165
5
3
Order By: Relevance
“…N:P ratios greater than 16 are generally representative of P limitation to productivity, relative to N availability, in humid tropical forests (47). In upper submontane and montane forests, N:P ratios < 16 suggest increasing N limitation relative to P, as recently detected in a field experiment in the Peruvian Andes (26). Low N:P was also found in particular portions of the Amazonian lowlands: extremely anoxic swamp environments are known areas of very low N availability relative to P (asterisks in Fig.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…N:P ratios greater than 16 are generally representative of P limitation to productivity, relative to N availability, in humid tropical forests (47). In upper submontane and montane forests, N:P ratios < 16 suggest increasing N limitation relative to P, as recently detected in a field experiment in the Peruvian Andes (26). Low N:P was also found in particular portions of the Amazonian lowlands: extremely anoxic swamp environments are known areas of very low N availability relative to P (asterisks in Fig.…”
mentioning
confidence: 67%
“…2, e). Tropical montane forests are generally viewed as N-limited ecosystems, relative to their lowland tropical forest counterparts (24)(25)(26). Particularly low soil N is known to occur on steep portions of hilly or montane tropical terrain, a result of low N residence time in soils (27).…”
mentioning
confidence: 99%
“…Some studies on tropical, and subtropical mountains, and subarctic tundra found that leaf N and P declined with altitude (Köhler et al 2006;Macek et al 2009;Soethe et al 2008;Sundqvist et al 2011). By contrast, other studies also showed that the N and P of leaves first increased and then decreased with increasing elevation on Mountain Gongga, China (Shi et al 2012) and in the Peruvian Andes (Fisher et al 2013). Meanwhile, Garkoti (2012) indicated that root N and P declined with elevation in the central Himalayas.…”
Section: Discussionmentioning
confidence: 89%
“…2015) and P limitation drives N:P variations among lowland Amazonian plots, explaining in particular variations between TAM‐05 and TAM‐06 (Asner and Martin 2011; Fisher et al. 2013). …”
Section: Discussionmentioning
confidence: 99%